The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1415-43662011000800015
|View full text |Cite
|
Sign up to set email alerts
|

Escória de siderurgia e seus efeitos nos teores de nutrientes e metais pesados em cana-de-açúcar

Abstract: RESUMOTipos de escórias se acumulam nos pátios das indústrias, tornando-se um problema ambiental, cuja disposição final em campos agrícolas é uma prática que pode minimizar a acumulação desses resíduos e, ao mesmo tempo, fornecer nutrientes às plantas e corrigir a acidez dos solos; apesar disto, há necessidade de se avaliar que riscos esses resíduos podem gerar ao ambiente. Objetivou-se, com este trabalho, avaliar a disposição final da escória de aciaria de forno elétrico e o fornecimento de silício, macronutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 12 publications
(2 reference statements)
2
6
0
9
Order By: Relevance
“…Corrêa et al (2008) and Sobral et al (2011) reported that the growing use of slag in agriculture is because silicate anions in slag compete with P for the same adsorption sites when they are adsorbed, preventing or hindering P adsorption. One advantage of silicate over limestone is its ability to make micronutrients available in the soil (Sobral et al, 2011).…”
Section: Treatments* Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corrêa et al (2008) and Sobral et al (2011) reported that the growing use of slag in agriculture is because silicate anions in slag compete with P for the same adsorption sites when they are adsorbed, preventing or hindering P adsorption. One advantage of silicate over limestone is its ability to make micronutrients available in the soil (Sobral et al, 2011).…”
Section: Treatments* Results and Discussionmentioning
confidence: 99%
“…Corrêa et al (2008) and Sobral et al (2011) reported that the growing use of slag in agriculture is because silicate anions in slag compete with P for the same adsorption sites when they are adsorbed, preventing or hindering P adsorption. One advantage of silicate over limestone is its ability to make micronutrients available in the soil (Sobral et al, 2011). When slag is used to neutralize soil acidity, the reduction in micronutrient availability due to the increased pH is minimized because steel slag has micronutrients in its chemical composition (Prado et al, 2002).…”
Section: Treatments* Results and Discussionmentioning
confidence: 99%
“…Com o intuito de controlar os valores de pH, deu-se início em Outubro de 2014 na ArcelorMittal Tubarão uma segunda etapa do experimento, com novas adequações no compartimento de pH, visando aprimorar seu desempenho. O uso da escória no tratamento de efluentes domésticos, se consolidado, somar-seia às já várias técnicas para o reaproveitamento da mesma [5,6], bem como poderia servir de impulso para novos usos, como o tratamento de efluentes de atividades rurais cujas características físico-químicas sejam semelhantes aos efluentes domésticos.…”
Section: Conclusãounclassified
“…A lama cal é um resíduo alcalino proveniente da fabricação de papel e celulose constituindo-se predominantemente de carbonato de cálcio e hidróxido de sódio. A escória de aciaria ou escória de siderurgia é um resíduo gerado pelas indústrias produtoras de ferro e aço e tem, como principal vantagem do seu uso, a redução do impacto ambiental (Sobral et al, 2011).…”
Section: Introductionunclassified